KOMPETENSI DALAM PENGOLAHAN LIMBAH RUMAH TANGGA MENJADI PUPUK ORAGNIK DI KOTA KENDARI - Laote, Muh. Yusril; Nalefo, La; Suriana, Suriana (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2024)
The quantity of waste generated by households is on the rise, yet the capacity of Kendari City to manage existing waste is diminishing. In order to facilitate the implementation of suitable measures for the processing of waste, it is essential to ensure that the community possesses the requisite competence. The objective of this study is to evaluate the competence of the processing of household waste into organic fertilizer in Kendari City. This study employs a qualitative research methodology. The research informants were selected using the purposive sampling technique, resulting in a total of one informant. Data were collected through observation, interviews, and document analysis with the assistance of interview guides created for this purpose. The data were analyzed qualitatively using the theory proposed by Miles & Huberman, namely data reduction, data presentation, and conclusion drawing. The findings indicate that competence in processing household waste into organic fertilizer in Kendari City is evident in the knowledge, attitudes, and skills possessed by the community in managing household waste into a useful and beneficial product such as organic fertilizer (search and solid). Effective waste management can facilitate a comprehensive and efficient approach that can positively impact the community in terms of health and the environment. Furthermore, it has the potential to serve as a source of income for the community. The processing of organic waste into organic fertilizer comprises six stages: collection and chopping of organic waste, mixing of organic waste into a composter, addition of MOL, closure of the composter, addition of organic waste and a second MOL, and sitting/fermentation of organic waste for 7 to 12 days.